2021
DOI: 10.1007/s00330-021-08010-9
|View full text |Cite
|
Sign up to set email alerts
|

Does it matter for the radiologists’ performance whether they read short or long batches in organized mammographic screening?

Abstract: Objective To analyze the association between radiologists’ performance and image position within a batch in screen reading of mammograms in Norway. Method We described true and false positives and true and false negatives by groups of image positions and batch sizes for 2,937,312 screen readings performed from 2012 to 2018. Mixed-effects models were used to obtain adjusted proportions of true and false positive, true and false negative, sensitivity, and sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 22 publications
1
10
1
Order By: Relevance
“…Laboratory studies have demonstrated that breast images induce robust adaptation, including selective adaptation effects based on mammographic breast density (Kompaniez et al, 2013; Kompaniez-Dunigan et al, 2015, 2018; Parthasarathy et al, 2023). This is consistent with clinical observation studies showing improved reading performance over the course of a batch (Abbey et al, 2020; Backmann et al, 2021; Taylor-Phillips et al, 2016). This provides convergent evidence for adaptation as a mechanism that impacts and can potentially improve performance in batch reading of screening mammograms.…”
Section: Adaptation To Specialized Environments – the Case Of Medical...supporting
confidence: 89%
“…Laboratory studies have demonstrated that breast images induce robust adaptation, including selective adaptation effects based on mammographic breast density (Kompaniez et al, 2013; Kompaniez-Dunigan et al, 2015, 2018; Parthasarathy et al, 2023). This is consistent with clinical observation studies showing improved reading performance over the course of a batch (Abbey et al, 2020; Backmann et al, 2021; Taylor-Phillips et al, 2016). This provides convergent evidence for adaptation as a mechanism that impacts and can potentially improve performance in batch reading of screening mammograms.…”
Section: Adaptation To Specialized Environments – the Case Of Medical...supporting
confidence: 89%
“…The overall performance of a screening program depends on organizational factors, image quality, and performance of the radiologists. Screen-reading is a perceptual task, and the radiologists’ performance might be influenced by reading volume and reading conditions [ 4 ]. We have previously shown that 23% of screen-detected cancers have a positive assessment score by only one of the two radiologists in BreastScreen Norway [ 5 ], and that 20–30% of the screen-detected and interval cancers are classified as missed in retrospective informed review studies [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is worth noting that the cancer rate in a screening study may be only 15.5 per 1000 [ 14 ], which suggests that radiologists spend most of their time reading normal scans without suspicious lesions. On the other hand, reading quality is also related to the total number of examinations and the position of the examination in the queue [ 15 ]. Short reading batches and risk-based reading queues may help further improve radiologists’ performance.…”
Section: Introductionmentioning
confidence: 99%